Implementasi Standar Akuntansi Pemerintah Berbasis Akrual Untuk Mewujudkan Laporan Keuangan Yang Berkualitas (Implementation of Accrual-Based Government Accounting Standards to Realize Quality Financial Reports) - Sari, Anita; Kusmilawaty, Kusmilawaty (STIE Malangkucecwara, 2023)
The goal of this research was to look into how the analyze whether quality financial reports are realized with the implementation of accrual-based SAP and how to implement accrual-based SAP in government offices in 2023with a focus on the Environment and Forestry Service of North Sumatra Province. Employees of the finance division of the Environment and Forestry Service of North Sumatra Province in 2023 were used in this study. This study employs qualitative research and data collection methods such as interviews, observations, and documentation According to the study's findings, the Government Accounting Standards on the Accrual Base have been fully implemented in the Environment and Forestry Service of North Sumatra Province in accordance with Government regulations, and there has been an improvement in the quality of financial statements that are more transparent and accountable